2018
DOI: 10.2105/ajph.2018.304514
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Overdose Mortality Among Former North Carolina Inmates: 2000–2015

Abstract: Former inmates are highly vulnerable to opioids and need urgent prevention measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
83
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 152 publications
(86 citation statements)
references
References 23 publications
1
83
1
1
Order By: Relevance
“…Third, the Consortium includes cohorts with a degree of heterogeneity and this is likely to have impacted the observed mortality estimates. For example, participants in several cohorts all have as inclusion criteria a history of opioid dependence [22,24,47] and/or a diagnosis of HIV [28,47,48], contributing to an increased risk of mortality. The impact of this cohort heterogeneity will be explored by conducting sensitivity analyses which exclude selected cohorts.…”
Section: Strengths and Weaknessesmentioning
confidence: 99%
“…Third, the Consortium includes cohorts with a degree of heterogeneity and this is likely to have impacted the observed mortality estimates. For example, participants in several cohorts all have as inclusion criteria a history of opioid dependence [22,24,47] and/or a diagnosis of HIV [28,47,48], contributing to an increased risk of mortality. The impact of this cohort heterogeneity will be explored by conducting sensitivity analyses which exclude selected cohorts.…”
Section: Strengths and Weaknessesmentioning
confidence: 99%
“…A recent study in North Carolina showed that the risk for OOD among inmates within two-weeks post-release from prison was 40 times higher than that of the general population; heroin carried an even greater risk, with recently released individuals being 74 times more likely than the general population to die from a heroin overdose (Ranapurwala et al, 2018). Furthermore, those receiving mental health services while incarcerated had almost twice the risk of OOD during the study period compared to those who did not receive mental health services (Ranapurwala et al, 2018). The increased vulnerability of this population demonstrates the importance of connection to communitybased services, specifically substance use treatment, prior to reentry into the community.…”
mentioning
confidence: 99%
“…Similarly, the absence of prescription records corresponding to medication assisted treatment (MAT) for OUD is a reflection of treatment practices and not the underlying prevalence. The need for MAT in prison and at release was highlighted by a recent North Carolina study which found that in the first two weeks following prison release, there was a 74 and 40 times greater risk of death from heroin and opioid overdose, respectively, as compared to the risks among those in the general population [24]. Although the need for OUD treatment during and following incarceration has gained significant attention in North Carolina and across the country, like other chronic health conditions, the health care resources for people released from prison are inadequate.…”
Section: Discussionmentioning
confidence: 99%